Polymorphisms of the QTL Region Associated with Shank Feathering in Chicken - Questan Ameen; Rana Al-Obaidi; Sadat Aziz; Sehand Arif; Mahdi Abdullah; Ahmed Shaker; Hani Hermiz; Basil Abbas; Adel Hussein (Basrah Journal of Veterinary Research)
A total of twenty-six local chickens were representing shank feathering and non-feathering shank were used to sequence five QTLs, which associated with shank feather trait in chicken. The five location sequence results were shown polymorphism between the shank feathering and non-feathering shank. All the candidate markers were differed between the shank feather and non-feathering shank. The big distance was in (ADL221), and the less distance was in marker MCW315.